SUFISTIC EDUCATION METHOD IN SIRAT AL-MUSTAQIM ACCORDING TO NURUDDIN AR-RANIRY'S PERSPECTIVE - Ahmad, Ahmad Liza (Journal of Contemporary Indonesian Islam, 2025)
Since its earliest emergence, Islamic education has served not only as a medium for transmitting religious knowledge but also as a process for cultivating moral character and spiritual consciousness. Within this framework, Sufism plays a crucial role as the esoteric dimension of Islam, aiming to purify the soul and bring individuals closer to God. This article explores the methods of Sufi education in Sirat al-Mustaqim, a seminal work by Nuruddin ar-Raniry, a prominent 17th-century scholar in the Aceh Sultanate. Employing a qualitative library research method and descriptive-historical analysis, this study reveals that Sirat al-Mustaqim integrates Sufi values such as tazkiyat al-nafs, riyadhah, muraqabah, muhasabah, and tajrid within its legal framework. Ar-Raniry’s approach emphasizes the balance between the exoteric and esotericaspects of Islam, aiming to develop the ideal human being. His spiritual pedagogy underscores sincerity, spiritual mentorship, and divine awareness, making this study highly relevant for addressing the contemporary neglect of spiritual dimensions in Islamic education. It also contributes to the revitalization of the intellectual legacy of the Nusantara in building a morally and spiritually grounded civilization.